(untitled) (Biological Sciences - PJSIR, 1999)
The Climate, soil types, agricultural seasons and the major crops of Bangladesh are briefly introduced. The interaction of crop duration and the climatic factors are graphically presented. Agroecological condi tions over which the major crops and their associated weeds are grown have been mentioned. The important weeds of major crops are commented on and acrop- wise list is appended. The species of great importance common to the whole country include Cyperus rotundus, Cynodon dactylon, Echinochloa crusgalli, Echinochloa colonum, Chenopodium album, Fimbristylis miliacea, Cyperus iria and Eicchornia crassipes. Two parasitic weeds newly introduced in the country, Striga densiflora and Orobanche indica are causing severe damage to sugarcane and mustard respectively.